STUDI KOMPARATIF: PERBANDINGAN ASPEK PENELITIAN TENTANG KAJIAN PENJURUBAHASAAN HUKUM DI INDONESIA DAN LUAR NEGERI - Febrian Febrian (Translation and Linguistics (Transling), 2023)
As a part of translation, oral translation is a branch of the field of translation that focusing on interpreting language orally. Practically, oral translation has several weaknesses, one of which is unavailable of final data output from the translation that can be studied. Therefore, this study aimed to explore and investigate more deeply related aspects that are often studied in the field of interpreting. This study used a qualitative research approach with a comparative study approach who tried to find the pattern phenomenon of the problem, especially in court interpreting research. The results of the data showed in the comparative review of several articles form, especially in the court interpreting fields on legal aspects carried out in Indonesia and overseas. The final result can be concluded that research related to interpreting in Indonesia studies more focused on product based oriented meanwhile, the research conducted of overseas which more focused on aspects of process based oriented of oral translation, especially in court interpreting.